2010
DOI: 10.1111/j.1600-0528.2010.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐rated oral health and associated factors in Brazilian elders

Abstract: Assessment and understanding of self-rated oral health should take into account social factors, subjective and clinical oral symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
97
4
25

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(146 citation statements)
references
References 48 publications
20
97
4
25
Order By: Relevance
“…In the Brazilian population, oral health conditions related to mastication are the most mentioned as a source of impact on performing daily activities 20 . The findings of strong relationship between appearance and self-reported oral health are consistent with other studies 21,[32][33][34][35] . This appreciation of physical appearance may happen because it is one of the most easily perceived features during social interactions, and it is suggested that the stereotype that "what is beautiful is good," meaning that a person with good looks is also seen as the owner of desirable social characteristics 36 .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In the Brazilian population, oral health conditions related to mastication are the most mentioned as a source of impact on performing daily activities 20 . The findings of strong relationship between appearance and self-reported oral health are consistent with other studies 21,[32][33][34][35] . This appreciation of physical appearance may happen because it is one of the most easily perceived features during social interactions, and it is suggested that the stereotype that "what is beautiful is good," meaning that a person with good looks is also seen as the owner of desirable social characteristics 36 .…”
Section: Discussionsupporting
confidence: 82%
“…Changing this perception over time is related to the onset and recovery of oral health diseases such as staining, cracking of restorations, and dental elements 41 . In terms of population, there are similar findings of the relationship between oral health self-perception and self-perception of oral appearance in Brazilian elderly 21,34 . This study has a recognized limitation: the absence of dental examination at the moment of data collection, which gives a lower strength to oral health data beyond the limitations inherent in the study of self-perceived health, a concept based on variable 25 and transient 25,42 , de forma transversal references, transversely.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…2 The way people handle dental problems can defers from one person to another due to many factors like work, fear, access to dental care and cost of treatment. 3 Most of the common dental problems patient's reports to dentists in the form of toothache are due to dental caries, gingivitis or periodontitis. The other problem is halitosis which gives the patients psychosocial trauma.…”
Section: Introductionmentioning
confidence: 99%